Structure–activity relationship study on senktide for development of novel potent neurokinin-3 receptor selective agonists1. Issue 3 (9th March 2015) - Misu, Ryosuke; Yamamoto, Koki; Yamada, Ai; Noguchi, Taro; Ohno, Hiroaki; Yamamura, Takashi; Okamura, Hiroaki; Matsuda, Fuko; Ohkura, Satoshi; Oishi, Shinya; Fujii, Nobutaka
<x xml:space="preserve">Abstract</x> A potent neurokinin-3 receptor (NK3R) selective agonist with resistance to proteolytic digestion was developed.